Clinical features and survival in pediatric oncohematological patients with COVID-19 in a referral Hospital of Peruvian Social Health Insurance, during 2020-2021 - Alvarado-Gamarra, Giancarlo (2023)
Introduction: In Latin America, there are few studies and heterogeneous results on pediatric oncohematology patients with COVID-19. Objective: To describe the clinical characteristics and survival of pediatric oncohematology patients with COVID-19 in a hospital in Lima-Peru, 2020-2021. Methods: Retrospective longitudinal study of hospitalized patients under 14 years of age. The data was collected from the medical records. Results: We included 30 patients, mostly men and schoolchildren, predominantly fever, respiratory and gastrointestinal symptoms, hematological neoplasia, and advanced oncological disease. The majority developed mild-moderate disease, but they also presented severe evolution requiring critical areas, with high mortality in hospitalization (13.3%) and low survival during follow-up (at 526 days, 59.26%, 95% CI 36 .53 to 76.20%). Survival increased with the start of chemotherapy, and decreased in patients in palliative condition, with respiratory support and shock. Conclusion: Most developed mild-moderate disease. However, SARS-CoV-2 can also cause severe involvement, death, and poor survival in oncohematological patients.